FASHION ACCOUTREMENTS: VERSATILITY FOR MULTI-UTILITY CLOTHING -“A FANTASY WARDROBE CONCEPT” - Mantri, Leela; Agarwal, Smriti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Today's young fashion consumers are seeking unique silhouettes to craft more appealing and aesthetic looks. The strong desire for individuality necessitates the exploration and utilization of basic silhouettes. Silhouettes serve as the core structure of the design, providing an authentic foundation upon which innovative solutions can be built. This study focuses on the redesign of additional articles of clothing for their multi-functional utility. Fashion accompaniments allow for the seamless integration of existing wardrobe pieces, significantly curbing excessive clothing consumption and waste, thus promoting sustainability. These versatile clothing pieces offer a range of styles, discouraging the need for frequent clothing purchases. This integrated approach can curb the impulsive buying habits among young fashion consumers presenting a creative solution for fashionable looks. The key is to familiarize customers with strategically planned wardrobes that include compatible detachable clothing pieces. Fashion accompaniments can be augmented to mix and match with existing wardrobe clothing pieces. Designers and fashion brands can be encouraged to focus on perennial clothing with a contemporary touch. It is crucial to educate consumers on the versatility of these accompaniments to effectively incorporate them into daily life. This study seeks to repurpose remnants from high fashion silhouettes into detachable pieces that can be transformed into new clothing designs. The adoption of simplified patternmaking concepts can minimize procurement costs. These silhouette overlays have the potential to revolutionize design and style experimentation, and traditional design boundaries. The transformation of basic shapes into versatile forms can unlock limitless possibilities for their optimal use, leading to an eco-friendly approach to fashion. The suitability of the silhouette to the figure type is a crucial factor in the selection process. The study proposed the implementation of CLO3D technology by brands to personalize looks and ascertain suitability to figure type for captivating results.